Social Class and the Division of Labour: Essays in Honour of Ilya Neustadt - Meiksins, Peter (Labour / Le Travail, 1985)
This article reviews the book, "Social Class and the Division of Labour: Essays in Honour of Ilya Neustadt," edited by Anthony Giddens and Gavin MacKenzie.
Keywords: LES syndicates britanniques sous les gouvernments travaillistes (Book); Nonfiction; RAVIER, Jean-Pierre; REVIEWS; books